Locally Recurrent Secretory Carcinoma of the Breast with NTRK3 Gene Fusion. (13th July 2021) - Mortensen, Lindsey; Ordulu, Zehra; Dagogo-Jack, Ibiayi; Bossuyt, Veerle; Winters, Loren; Taghian, Alphonse; Smith, Barbara L.; Ellisen, Leif W.; Kiedrowski, Lesli A.; Lennerz, Jochen K.; Bardia, Aditya; Spring, Laura M.
Abstract: Enhanced understanding of the molecular events underlying oncogenesis has led to the development of "tumor-agnostic" treatment strategies, which aim to target a tumor's genomic profile regardless of its anatomic site of origin. A classic example is the translocation resulting in an ETV6 - NTRK3 gene fusion, a characteristic driver of a histologically diverse array of cancers. The chimeric ETV6 - NTRK3 fusion protein elicits constitutive activation of the tropomyosin receptor kinase (TRK) C protein, leading to increased cell survival, growth, and proliferation. Two TRK inhibitors, larotrectinib and entrectinib, are currently approved for use in the metastatic setting for the treatment of advanced solid tumors harboring NTRK fusions. Here we report a rare case of recurrent secretory carcinoma of the breast (SCB) with NTRK3 gene fusion. Whereas most cases of SCB represent slow-growing tumors with favorable outcomes, the case detailed here is the first to the authors' knowledge of recurrence within 1 year of surgery. We review the molecular findings and potential clinical significance. Key Points : The translocation resulting in the ETV6 - NTRK3 gene fusion is a known oncogenic driver characteristic of secretory carcinoma of the breast (SCB). Whereas most cases of SCB represent slow-growing tumors with favorable outcomes, the case here with ETV6 - NTRK3 gene fusion had local recurrence within 1 year of surgery. Two tropomyosin receptor kinase (TRK) inhibitors, larotrectinib and entrectinib, are approved to treat NTRK fusion–positive tumors, demonstrating sustained high overall response rates in the metastatic setting. Approval of TRK inhibitors necessitates optimization of NTRK fusion detection assays, including detection with liquid biopsies. Abstract : This article reports a rare case of recurrent secretory carcinoma of the breast with NTRK3 gene fusion, detailing the molecular findings and potential clinical significance.